Pengaruh Penggunaan Iklan dan Celebrity Endorser di Instagram terhadap Minat Beli Followers (Studi Kasus pada Followers Aktif Akun Instagram @merche.id) - Endah Fantini; Rifan Ardianto (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
The purpose of this study was to analyze and find out the effect of the use of advertising and celebrity endorsers on Instagram on the buying interest of followers of the @merche.id Instagram account. The data was collected by distributing questionnaires to 100 respondents who were active followers of the @merche.id Instagram account. The sampling was carried out using the Slovin formula. The analytical tools used were simple linear regression, multiple linear regression, and classical assumption tests, carried out as requirements that must be met in performing linear regression analysis (simple and multiple). The hypothesis testing was carried out simultaneously using the F test and partially using the T-test. The results showed that there was a significant effect of the use of advertisements and celebrity endorsers on followers' buying interest, which was 84.9% and the rest was influenced by variables that were not investigated further.